(untitled) (Historia, 2025)
By the early 1960s, South Africa faced increasing international pressure due to its policy of apartheid. This pressure took many forms, among them a sports boycott of racially segregated sports during the apartheid era. The International Olympic Committee (IOC) was one sporting body who issued an ultimatum to the South African National Olympic Committee (SANOC) to abandon racial discrimination in sport or face possible exclusion from the 1964 Tokyo Olympics. This set in motion a ‘counter-offensive’ by the South African government to stage the first in a number of organised sports meetings they called the ’SA Games’; a model of the Olympic Games presented in South Africa. Although the international sports boycott on South Africa has received adequate attention from academics – some of whom have traced and analysed its origins and, in certain instances, focused on its impact on specific sporting codes – the response to these boycotts at home, and in particular, the staging of an apartheid version of the Olympics, has not been researched adequately. This paper addresses that lacuna and studies the staging of various sports meetings known as the SA Games, a largely forgotten episode of South African sports history.